2019
DOI: 10.12944/crnfsj.7.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Textural Properties, Resistant Starch, and in Vitro Starch Digestibility as Affected by Parboiling of Brown Glutinous Rice in a Retort Pouch

Abstract: The effects that two preparation methods (parboiling with different degrees of gelatinization and parboiling with enzymatic hydrolysis) have on the qualities of brown glutinous rice were investigated in order to optimize the pretreatment conditions of brown glutinous rice for the ready-to-eat product in retort pouch. The brown glutinous rice was parboiled at various temperatures (50, 70 and 90C) and steamed at atmospheric pressure until the gelatinize level of 60, 80 and 100%. For the parboiling with enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A similar research study found that total reducing sugar contents increased sharply in the 16‐month storage period and thereafter, increased steadily. The rate of reduction in sugar content out of total sugar content increased with extended storage duration (Wiruch et al, 2019 ). In another study, Devraj et al reported significant reductions of 26.4–64.7% and 37.1–52.1% in the content of disaccharides, that is, sucrose and polysaccharides, that is, raffinose, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar research study found that total reducing sugar contents increased sharply in the 16‐month storage period and thereafter, increased steadily. The rate of reduction in sugar content out of total sugar content increased with extended storage duration (Wiruch et al, 2019 ). In another study, Devraj et al reported significant reductions of 26.4–64.7% and 37.1–52.1% in the content of disaccharides, that is, sucrose and polysaccharides, that is, raffinose, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A similar research study found that total reducing sugar contents increased sharply in the 16month storage period and thereafter, increased steadily. The rate of reduction in sugar content out of total sugar content increased with extended storage duration (Wiruch et al, 2019)…”
Section: Effect Of Storage On Simple Sugars Of Brown Ricementioning
confidence: 95%
“…Starch containing higher amylose tended to have a greater amount of amylose-lipid complex. As a result, the molecular formations potentially prevent starch chains from starch digesting enzymes [ 10 , 17 , 47 ]. This could result in a higher resistance to enzyme hydrolysis of rice starch, and thus a higher RS content [ 10 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the molecular formations potentially prevent starch chains from starch digesting enzymes [ 10 , 17 , 47 ]. This could result in a higher resistance to enzyme hydrolysis of rice starch, and thus a higher RS content [ 10 , 47 ]. In addition, it was also shown that the ability to resist the enzymatic digestion of rice starch is attributed to its large granule size [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation